Environmental stewardship and sustainable development - Jain, R. B. (New Delhi : Friedrich Ebert Stiftung, 1997)
Seminar papers.
Includes bibliographical references and index.
Moklesur
Keywords: Sustainable development -- India -- Congresses; Environmental policy -- India -- Congresses